2015
DOI: 10.1186/s13058-015-0593-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling of the pubertal mouse mammary gland identifies miR-184 as a candidate breast tumour suppressor gene

Abstract: IntroductionThe study of mammalian development has offered many insights into the molecular aetiology of cancer. We previously used analysis of mammary morphogenesis to discover a critical role for GATA-3 in mammary developmental and carcinogenesis. In recent years an important role for microRNAs (miRNAs) in a myriad of cellular processes in development and in oncogenesis has emerged.MethodsmicroRNA profiling was conducted on stromal and epithelial cellular subsets microdissected from the pubertal mouse mammar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 80 publications
2
35
0
Order By: Relevance
“…It has been demonstrated that miRNAs play crucial roles in cell biology such as proliferation, apoptosis, cell cycle, migration and invasion 13, 14, 15. Increasing evidence shows the potential involvement of miRNAs in the development of various human cancers such as gastric cancer, bladder cancer, lung cancer, hepatocellular carcinoma, and breast cancer 16, 17, 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that miRNAs play crucial roles in cell biology such as proliferation, apoptosis, cell cycle, migration and invasion 13, 14, 15. Increasing evidence shows the potential involvement of miRNAs in the development of various human cancers such as gastric cancer, bladder cancer, lung cancer, hepatocellular carcinoma, and breast cancer 16, 17, 18, 19.…”
Section: Introductionmentioning
confidence: 99%
“…41 As suggested by various studies, miR-184 might be a useful diagnostic and therapeutic tool for malignant diseases. 38,39 However, to the best of our knowledge, ours is the first study to provide data about miR-184 expression in EC.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, miR-184 functions as a tumor suppressor in various cancers (renal carcinoma, 36 glioma, 37,38 non-small-cell lung cancer, 39 oral squamous cell carcinoma, 40 breast cancer 41 ) by repressing oncogenes such as TNFAIP2, 37 SND1, 38 CDC25A, c-MYC, 39 and regulating the AKT/mTORC1 pathway. 41 As suggested by various studies, miR-184 might be a useful diagnostic and therapeutic tool for malignant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There may be a possibility of increased miR-206 levels due to BRCA1 loss, culminating in mammary gland remodeling and tumour development 20 . miR-184 is found to be a tumour suppressor by regulating the number of genes in the PI3K/AKT/mTOR pathway, as observed by miR profiling of the pubertal mouse mammary gland 21 . This pathway is important in mammary gland development and lactation 22 .…”
Section: Mirs Controlling Involution and Breast Cancermentioning
confidence: 81%
“…This pathway is important in mammary gland development and lactation 22 . miR-184 is only expressed in epithelial cells, and the level increases during differentiation of cells from terminal end bud into ductal epithelial cells 21 .…”
Section: Mirs Controlling Involution and Breast Cancermentioning
confidence: 99%